2009
DOI: 10.1080/13803390802232667
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of episodic memory following moderate to severe traumatic brain injury during inpatient rehabilitation

Abstract: We examined memory self-awareness and memory self-monitoring abilities during inpatient rehabilitation in participants with moderate to severe traumatic brain injury (TBI). Twenty-nine participants with moderate to severe TBI and 29 controls matched on age, gender, and education completed a performance prediction paradigm. To assess memory self-awareness, participants predicted the amount of information they would remember before completing list-learning and visual-spatial memory tasks. Memory self-monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…After being read descriptions of verbal and visual memory tasks, participants provided an estimate of how well they thought they would perform on the memory tasks. Consistent with previous findings, participants with TBI were expected to perform more poorly on the memory tasks than control participants [4,5,18]. Based on prior literature showing intact self-awareness of memory using performance-prediction paradigms [5], it was hypothesized that individuals with TBI would be as accurate as control participants predicting their memory performance when assessed with a specific, temporally proximal online assessment technique.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…After being read descriptions of verbal and visual memory tasks, participants provided an estimate of how well they thought they would perform on the memory tasks. Consistent with previous findings, participants with TBI were expected to perform more poorly on the memory tasks than control participants [4,5,18]. Based on prior literature showing intact self-awareness of memory using performance-prediction paradigms [5], it was hypothesized that individuals with TBI would be as accurate as control participants predicting their memory performance when assessed with a specific, temporally proximal online assessment technique.…”
Section: Introductionmentioning
confidence: 85%
“…These self-report judgements require participants to provide estimates of their memory functioning in close temporal proximity to memory tests. In contrast to offline assessment techniques, the majority of studies using online assessment methodologies have found intact memory self-awareness in individuals after TBI [5,14,15]. For example, using a global performance-prediction paradigm, Anderson and Schmitter-Edgecombe [5] found that individuals with moderate-to-severe TBI who were less than 3 months post-injury demonstrated preserved metamemorial abilities.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations